Effects of mesenchymal stem cells transplantation on multiple sclerosis patients. (December 2020) - Barati, Shirin; Tahmasebi, Fatemeh; Faghihi, Faeze
Abstract: Multiple Sclerosis (MS) is a demyelinating autoimmune disease of the central nervous system (CNS) with symptoms such as neuroinflammation and axonal degeneration. Existing drugs help reduce inflammatory conditions and protect CNS from demyelination and axonal damage; however, these drugs are unable to enhance axonal repair and remyelination. In this regard, cell therapy is considered as a promising regenerative approach to MS treatment. High immunomodulatory capacity, neuro-differentiation and neuroprotection properties have made Mesenchymal Stem Cells (MSCs) particularly useful for regenerative medicine. There are scant studies on the role of MSCs in patients suffering from MS. The low number of MS patients and the lack of control groups in these studies may explain the lack of beneficial effects of MSC transplantation in cell therapies. In this review, we evaluated the beneficial effects of MSC transplantation in clinical studies in terms of immunomodulatory, remyelinating and neuroprotecting properties of MSCs.